Seeking the source of adipocytes in adult white adipose tissues - Lee, Yun-Hee (Landes Bioscience, 2012)
Adipocyte progenitors are thought to play a fundamental role in white adipose tissue (WAT) plasticity, which enables dynamic modulation of WAT metabolic and cellular characteristics in response to various stimuli. In general, two main strategies have been used to identify adipocyte progenitor cells: fluorescence-activated cell sorting (FACS)-based prospective analysis and lineage tracing. Although FACS-isolation is highly useful in defining multipotential stem cell populations for in vitro analysis and transplantation, lineage tracing is essential to identify endogenous progenitors that do, in fact, differentiate into adipocytes in vivo. Our recent lineage tracing studies have shown that cells expressing the surface marker platelet-derived growth factor receptor α (PDGFRα) give rise to white and brown adipocytes in adult WAT, depending on inductive cues. PDGFRα(+) cells are a subpopulation of those expressing CD34 and Sca1, and have unique morphology whereby long dendritic processes contact numerous cell types in the microenvironment. The significant contribution of PDGFRα(+) cells to browning and hyperplastic expansion of WAT leads us to propose that PDGFRα(+) cells are remodeling stem cells in adult WAT. Application of advanced imaging technology and genetic tools to this progenitor population will allow greater understanding of cellular plasticity in adipose tissue.